THE ANALYSIS OF DENOTATIVE AND CONNOTATIVE MEANING OF INDONESIAN SEXIST METAPHORS - Putriahyana Sucianingrum; Tutur Nur Utami; Patricia Marceline P.G. T. (ELTR Journal, 2019)
This research was conducted to analyse the denotative and connotative meaning of Indonesian sexist metaphors. The metaphors were collected from various sources, such as online sources, Indonesian Dictionary (KBBI), song lyrics, poems, movies, and newspaper. There were two research questions formulated as follows: 1) What are the Indonesian sexist metaphors? and 2) What are the denotative and connotative meaning of the sexist metaphors? The method of this research was qualitative method, specifically content analysis. This method has two sources, they are primary and secondary sources. The primary source was the metaphors found in various sources. The secondary sources were theories of metaphor, denotative and connotative meaning, and sexist language. The metaphors were analysed using Lakoff and Johnson’s theory (1980) and the meaning of the metaphor was analysed using Parera’s theory (2004). In identifying the sexist in the metaphor, this study used the sexist language theory from Mills (1995). The results of this research showed that there were 32 Indonesian sexist metaphors, 16 of which belonged to female and the other 16 to male. Each metaphor had both connotative and denotative meanings. Based on the findings, it could be concluded that Indonesian language has sexist metaphors for both male and female.